Continuum Field Model of Street Canyon: Numerical Examples. Part 2 - M.M. Duras (Engineering Transactions, 2015)
Continuum field control model of a street canyon is considered. The six separate monocriterial optimal control problems consist of minimization of functionals of the total travel time, of global emissions of pollutants, and of global concentrations of pollutants, both in the studied street canyon, and in its two nearest neighbour substitute canyons, respectively. The six optimization problems for the functionals are solved numerically. General traffic control issues are inferred. The discretization method, comparison with experiment, mathematical issues, and programming issues, are presented.